The Unintended Consequence of Novel Coronavirus (COVID-19) Pandemic on Racial Inequities Associated With Adverse Childhood Experiences (ACEs): Findings From a Population-Based Study - Srivastav, Aditi; Richard, Chelsea L.; McRell, Amanda S.; Strompolis, Melissa (Frontiers in Public Health, 2021)
A rising concern is the COVID-19 pandemic effect on adverse childhood experiences (ACEs) due to increased parental stress and social/physical isolation. These pandemic effects are likely to be higher in already marginalized communities. The objective of this ecological study was to examine the relationship between COVID-19 cases and deaths, race/ethnicity, and the estimated number of adults with ACEs using data from South Carolina (SC). COVID-19 reported cases and death data were obtained from the SC Department of Health and Environmental Control. ACE data was used from the 2014-2016 SC Behavioral Risk Factor Surveillance System. Census data were used to obtain county population data. To measure the relationship between these variables, the Spearman rank-order correlation test was used because the data distribution was non-normal. There was a moderate relationship between the estimated number of adults with one or more ACEs and deaths (ρ = 0.89) and race/ethnicity-specific COVID-19 case counts by county (Black: ρ = 0.76; =White: ρ = 0.96; Hispanic: ρ = 0.89). Further, the Spearman correlation test showed the strongest relationship between COVID-19 deaths and race-ethnicity-specific county populations was with the Black adult population (ρ = 0.90). Given the known link between existing health inequities and exposure to COVID-19, these results demonstrate that the current pandemic could have unintended consequences on the well-being of children and caregivers. Response efforts should consider promoting protective factors for children and families and advocating for equitable policies and systems that serve children.